The Implementation of Role Play Method for Improving Speaking Skills in Grade 11 at SMAN 1 Kisaran - Panjaitan, Ruth; Sri Rahayu (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research explores how role play activities can transform English speaking skills among Grade 11 students at SMAN 1 Kisaran. The study was conducted using a quasi-experimental design with 60 students divided into experimental and control groups over 8 weeks. The experimental group participated in structured role play sessions three times per week, engaging in scenarios like restaurant conversations, job interviews, and shopping dialogues. Data was collected through pre-tests, post-tests, classroom observations, and confidence surveys. The findings show remarkable improvements: students in the role play group increased their speaking fluency by 38%, accuracy by 35%, pronunciation by 29%, and confidence by 42% compared to the control group. The research demonstrates that role play creates an engaging, low-pressure environment where students naturally develop their speaking skills by "becoming" different characters, which reduces anxiety and encourages experimentation with the language. The study concludes that role play should be integrated as a core teaching strategy in Indonesian high schools to address students' fear of speaking English, making language learning more effective and enjoyable.